1999
DOI: 10.1128/cdli.6.2.186-192.1999
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Influenza Virus Infection of Mice Fed Bifidobacterium breve YIT4064

Abstract: Mice fed Bifidobacterium breve YIT4064 and immunized orally with influenza virus were more strongly protected against influenza virus infection of the lower respiratory tract than ones immunized with influenza virus only. The number of mice with enhanced anti-influenza virus immunoglobulin G (IgG) in serum upon oral administration of B. breve YIT4064 and oral immunization with influenza virus was significantly greater than that upon oral immunization with influenza virus only. These findings demonstrated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 28 publications
1
56
0
Order By: Relevance
“…The influenza A ⁄ PR ⁄ 8 ⁄ 34 (PR8, H1N1) virus was grown in the allantoic sacs of 11-day-old chicken embryos for 2 days at 34°C by a previously reported method (Yasui et al 1999). The allantoic fluid was removed and stored at )80°C.…”
Section: Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…The influenza A ⁄ PR ⁄ 8 ⁄ 34 (PR8, H1N1) virus was grown in the allantoic sacs of 11-day-old chicken embryos for 2 days at 34°C by a previously reported method (Yasui et al 1999). The allantoic fluid was removed and stored at )80°C.…”
Section: Virusmentioning
confidence: 99%
“…Increasing evidence supporting the role of probiotics, e.g. Lactobacillus rhamnosus GG (LGG) and Lactobacillus casei Shirota (LcS), in the prevention and ⁄ or treatment of several diseases, including bacterial and viral infections in the gastrointestinal and respiratory systems, such as IFV infection, has been reported (Saxelin et al 1998;Yasui et al 1999Yasui et al , 2004Hori et al 2001Hori et al , 2002Goldin and Gorbach 2008). However, such potential health benefits of probiotic bacteria against IFV infection need to be supported by additional scientific evidence.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been suggested that viable bifidobacteria exert their healthpromoting effects on the host via their metabolism and metabolites. In contrast, cell components of Bifidobacterium unrelated to whether the cells are viable or dead have been proposed to stimulate immune function (Leahy et al 2005;Ló pez et al 2010;Yasui et al 1999). Consequently, there is a need to separately enumerate viable and dead cells if we are to understand the role of BbrY as a probiotic.…”
Section: Discussionmentioning
confidence: 99%
“…However, the number determined by the former method included both viable and dead cells. Although bifidobacteria have beneficial effects in both the live and dead state (Ló pez et al 2010;Yasui et al 1999;Young et al 2004), live cells can proliferate and secrete beneficial factors. It is therefore important to be able to discriminate viable cells from dead cells to characterize the usefulness of BbrY as a probiotic.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies of respiratory tract pathogens have focussed on in£uenza virus. Yasui et al [51] investigated the ability of feeding mice with B. breve (strain YIT4064) to augment the antibody response to oral in£uenza virus vaccination and thus a¡ect protection against intra-nasal virus challenge ; they showed that B. breve-fed/virus-vaccinated mice showed a markedly increased survival rate against in£uenza challenge compared to control-fed/virus-vaccinated mice, and that a signi¢cantly greater number of these animals developed high serum anti-in£uenza virus-speci¢c IgG class antibody titres. A recent study by Hori et al [52] has shown that feeding mice with L. casei (Shirota) prior to intra-nasal in£uenza virus challenge can confer a signi¢cant increase in protection to the upper respiratory tract.…”
Section: Recent Advances: Probiotic-mediated Immunementioning
confidence: 99%